Peningkatan Hasil Belajar Mahasiswa PGSD Materi Kecepatan Menggunakan Fast Trick - Nugraini, Frisca Anghi; Ramadhan, Fahmi Hasan (Elementary Education Journal, 2023)
Background: Education is very important in the current era of globalization. The purpose of education is to grow and develop the potential of students to become individuals who have knowledge, skills, are independent, and are civilized. UMS PGSD students are expected to take various courses and achieve the desired competencies, including the Basic Science Concepts course. To improve learning outcomes, one alternative that can be done is to develop students' understanding using fast formulas or "fast tricks". The research objective was to improve the learning outcomes of PGSD students by optimizing the use of fast tricks. Thus, it is hoped that students can gain more meaningful knowledge and achieve better learning outcomes. Method: This study used the classroom action research (PTK) method which was carried out directly by the researcher with cycles of planning, implementing, observing, and reflecting. Result: The research was conducted at the Muhammadiyah University of Surakarta with research subjects in the form of 10 fourth semester PGSD students. It is hoped that this research can contribute to increasing understanding and learning achievement of PGSD students. The fast trick method is still used, and there is an increase in the percentage of completeness resulting from understanding the basic science concepts. Implication: The implications of this study are: First, the elementary schools' headmasters in Indonesia should enrich the teachers' knowledge and insight related to PTK and fast trick. Second, the government, supported by researchers, has to design an excellent assessment system to solve time limitations. Novelty: The present study revealed the implementation of fast trick in elementary school comprehensively.